Perceived social support and Chinese university students’ intentions to participate in non-traditional sports: a moderated chain mediation model - Zhang, Ying; Wang, Mengkai; Zhang, Yongtao (Frontiers in Psychology, 2025)
AimThis study investigates how perceived social support influences Chinese university students’ willingness to participate in non-traditional sports, focusing on the chain mediating roles of psychological resilience and self-efficacy, and the moderating effect of Collectivistic orientation.MethodsAn online survey collected 540 valid responses from Chinese university students. The survey measured perceived social support from family, friends, and significant others; psychological resilience; self-efficacy; and participation intention in non-traditional sports. Main effects and mediation effects were tested using SPSS Process model 6, while moderation effects were examined using Process model 83.ResultsThis study revealed that perceived social support positively influences Chinese students’ participation intention in non-traditional sports. Both psychological resilience and self-efficacy partially mediate this relationship, with evidence supporting a sequential mediation pathway. Moreover, the positive effect of perceived social support on psychological resilience is significantly stronger among individuals with a collectivistic orientation, confirming the moderating role.ConclusionThis study demonstrates that perceived social support significantly enhances participation intention in non-traditional sports among Chinese university students. The chain mediating roles of psychological resilience and self-efficacy, coupled with the moderating influence of cultural orientation, provide valuable insights for promoting non-traditional sports by addressing both psychological and cultural factors.